2021
DOI: 10.1186/s12939-021-01435-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based disparities on health indices during COVID-19 crisis: a nationwide cross-sectional study in Jordan

Abstract: Background COVID-19 has an inevitable burden on public health, potentially widening the gender gap in healthcare and the economy. We aimed to assess gender-based desparities during COVID-19 in Jordan in terms of health indices, mental well-being and economic burden. Methods A nationally representative sample of 1300 participants ≥18 years living in Jordan were selected using stratified random sampling. Data were collected via telephone interviews i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…In addition, it is the major referral center for all of central Jordan serving more than four million patients [ 23 ]. JUH treats more than half a million patients annually and conducts about 25,000 surgical operations every single year [ 24 ]. According to the Joint Commission International (JCI) accreditation rating, JUH is ranked number one and 18th at the Middle Eastern and global levels in terms of quality excellence, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it is the major referral center for all of central Jordan serving more than four million patients [ 23 ]. JUH treats more than half a million patients annually and conducts about 25,000 surgical operations every single year [ 24 ]. According to the Joint Commission International (JCI) accreditation rating, JUH is ranked number one and 18th at the Middle Eastern and global levels in terms of quality excellence, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A cross-section study conducted in Jordan held telephone interviews with 1300 participants (men and women) to address gender-based disparities during COVID-19 including health indices, mental well-being and economic burden 27 . The study showed that women in Jordan are experiencing worse outcomes in terms of mental well-being and economic burden, which may widen the gender gap issue.…”
Section: Discussionmentioning
confidence: 99%
“…En ese escenario, el estado emocional propio de estas mujeres se ve afectado triplemente: no solo por sus condiciones sociodemográficas anteriormente descritas (que sean mujeres, que sean migrantes, que pertenezcan principalmente al sector laboral que trabaja en la informalidad y que estén en situación de pobreza [Ramírez Lasso, 2018, p. 47]), sino porque en un contexto de crisis mundial y nacional, su propio contexto local les genera mayor estrés y contribuye poco a mejorar esta situación. En ese sentido, las afectaciones en la salud mental de las mujeres venezolanas migrantes coinciden con lo hallado en casos como Jordania, donde las mujeres se han visto más afectadas que los hombres en su bienestar mental y carga económica (Abufaraj et al, 2021).…”
Section: Discusión Y Conclusionesunclassified